Mesoporous metal-oxide-semiconductor capacitors detect intra-porous fluid changes - Gimenez, Rocío (2017)
Real-time measurements of fluidic phenomena inside nano/mesoporous films offer an alternative way to study fundamental processes, as well as to explore novel applications. Most current techniques use optical measurement methods or microgravimetric approaches. Here it is shown that a metal-oxide-semiconductor(MOS) capacitor can be used to detect fluidic transport inside mesoporous networks. The MOS stack, which consists of two contacts (Cu and silicon) separated by a supramolecularly templated mesoporous oxide film to form a MOS capacitor, detects fluid changes that can be quantified from an effective permittivity model ofmesoporous structures interacting with a fluid. The device was used to monitor liquids infiltration and subsequent evaporation in both titania and silica mesoporous films. It was observed how the evaporation dynamics significantly depends on film characteristics and fluid properties.